Analisis PESTEL Terhadap Ketahanan Sistem Manajemen Keuangan Bank Syariah Di Era Ketidakpastian Global - Saripudin; Tiolina Evi Nausta Pardede (ITB AAS Indonesia Surakarta, 2026)
Global uncertainty characterized by economic dynamics, regulatory changes, technological disruption, and social shifts demands that Islamic banks have adaptive and resilient financial management systems. This study aims to develop a conceptual framework that explains the role of factors within the PESTEL approach to the resilience of Islamic banks' financial management systems. This research uses a qualitative approach based on conceptual papers, using literature reviews and conceptual synthesis of various relevant scientific studies. The study results produce a conceptual model that positions political, economic, social, technological, environmental, and legal factors as external determinants that influence financial management systems through the mechanism of organizational adaptability (dynamic capability). This model confirms that the resilience of Islamic banks' financial systems is influenced not only by internal factors but also by the dynamic interaction between external environmental pressures and the organization's adaptive capacity. This research contributes to enriching the Islamic financial management literature by integrating the PESTEL approach and the concept of financial system resilience. It also offers a conceptual basis for further empirical research and the development of adaptive strategies in the face of global uncertainty.